Investigation of apoptosis in cultured cells infected with equine herpesvirus 1 - Scrochi, Mariela Rita (2017)
Many viruses alter different stages of apoptosis of infected cells as a strategy for successful infection. Few studies have addressed mechanisms of equine herpesvirus 1 (EHV-1) strain-induced cell death. We investigated the effect of an abortigenic strain (AR8 strain) on heterologous Madin–Darby bovine kidney cells and homologous equine dermis (ED) cells cell lines. We compared morphologic and biochemical features of early and late apoptosis at different postinfection times. We investigated translocation of phosphatidylserine to the cell surface, nuclear fragmentation and changes in the cytoskeleton using flow cytometry and annexin V/propidium iodide staining, DNA laddering, terminal deoxynucleotidyl transferase UTP nick-end labeling assay and immunofluorescence staining of cytokeratin 18 cleavage. AR8 EVH-1 strain interfered with apoptosis in both cell lines, particularly during the middle stage of the replication cycle; this was more evident in ED cells. Although this antiapoptotic effect has been reported for other alpha herpesviruses, our findings may help elucidate how EHV-1 improves its infectivity during its cycle.